O20 Marginal zone B cell development from early T2 progenitors is defective in lupus nephritis. (23rd March 2020) - Tull, Thomas J; Guesdon, William; Robson, Michael G; D'Cruz, David; Bemark, Mats; Spencer, Jo
Abstract : Background: Marginal zone B cells (MZB) are a distinct B cell subset but the site and nature of their differentiation in humans is not understood. In mice, MZB are formed from transitional T2 cells shortly after exit from the bone marrow into the blood. Here we demonstrate a human MZB maturation axis that emerges at the T2 stage that collapses in lupus nephritis (LN). Methods: Mass cytometry was used to phenotype B cells from blood and gut-associated lymphoid tissue (GALT) from healthy donors (HCD). Single cell RNA sequencing was performed using a 10X genomics platform. Flow and mass cytometry were used to investigate MZB differentiation in LN. Results: Deep phenotypic analysis of B cells from HCD revealed prominent IgM hi and IgM lo TS cell populations emerge at the T2 stage and phenotypically align with IgM hi CD45RB hi marginal zone precursor cells (MZP). IgM hi TS cells had high expression of the gut homing receptor α4β7 integrin and were grossly enriched in GALT. IgM hi TS B cells produced IL-10 and were enriched in retinoic acid and lipopolysaccharide genes consistent with exposure to the gut microenvironment. MZB depletion was seen in LN alongside depletion of MZP and TS IgM hi cells, suggesting collapse of this maturational axis. Conclusion: We identify a bifurcation of human B cell development that starts at the T2 stage and gives rise to a gut homing IgM hi branch that is functionally and phenotypically distinct. The depletion of this branch in patients with LN affirms its existence in health, but also has important disease implications, such as the susceptibility of LN patients to pneumococcal infections and diminished B regulatory responses seen in the disease. Acknowledgements: This work was funded by the Medical Research Council of Great Britain (MR/R000964/1) and The Lupus Trust.